2001
DOI: 10.1002/1097-4652(2001)9999:9999<::aid-jcp1060>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Gene directed enzyme/prodrug therapy of cancer: Historical appraisal and future prospectives

Abstract: Gene therapy of cancer is a novel approach with the potential to selectively eradicate tumour cells, whilst sparing normal tissue from damage. In particular, gene-directed enzyme prodrug therapy (GDEPT) is based on the delivery of a gene that encodes an enzyme which is non-toxic per se, but is able to convert a prodrug into a potent cytotoxin. Several GDEPT systems have been investigated so far, demonstrating effectiveness in both tissue culture and animal models. Based on these encouraging results, phase I/II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
146
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(150 citation statements)
references
References 129 publications
2
146
0
2
Order By: Relevance
“…[36][37][38] Others have also shown 5-FC conversion to 5-FU in patients receiving cytosine deaminase gene delivered via nonreplicating adenoviral vectors. 38,39 These preliminary results support future investigation of TAPET-CD at higher doses via intratumoral injection. However, since local regional therapeutics have limited utility in oncology a secondgeneration Salmonella vector expressing CD is undergoing preclinical development for potential intravenous injection.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Others have also shown 5-FC conversion to 5-FU in patients receiving cytosine deaminase gene delivered via nonreplicating adenoviral vectors. 38,39 These preliminary results support future investigation of TAPET-CD at higher doses via intratumoral injection. However, since local regional therapeutics have limited utility in oncology a secondgeneration Salmonella vector expressing CD is undergoing preclinical development for potential intravenous injection.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The rationale for this type of therapy is to increase the therapeutic index in cancer treatment. 3 Transfer of the herpes simplex virus type 1 thymidine kinase (HSV-TK) gene into tumor cells sensitizes them to the antiviral drug ganciclovir (GCV). [4][5][6][7] Numerous studies have demonstrated excellent cell killing with GCV in HSV-TK-expressing tumor cells both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Other gene therapies for human colorectal cancer, such as enzyme/prodrug systems (HSVtk/ganciclovir; CD/5-fluorocytosine) and immune-gene therapy based on cytokine or tumor antigen expression to induce tumor immunity (eg CEA), have not yet improved prognosis. 4,[5][6][7] Elucidation of the basic molecular mechanisms of colorectal cancer and determination of a novel target for gene therapy are thus required.…”
Section: Introductionmentioning
confidence: 99%